Operational blue water footprint and water deficit assessment of coal-fired power plants: case study in Malaysia - Mardi N.H.; Ean L.W.; Malek M.A.; Chua K.H.; Ahmed A.N. (Springer, 2024)
Freshwater is an essential resource used to generate electricity at coal-fired power plants. Previous literature has shown that a few states in Malaysia will face a high risk of water stress. Hence, coal-fired power plants located at risk states are exposed to potential water risk. This study aims (i) to determine the operational blue water footprint at coal-fired power plant from 2009 until 2020